Evaluation of Prophet Muhammad’s techniques in managing misbehaviors: application in primary school classrooms - Wan Yusoff, Wan Mazwati; Abdullah, Asyraff Hafdzan (Mediterranean Center of Social and Educational Research Publishing, Rome-Italy, 2015)
Studies have shown that there is a correlation between troublesome classroom behaviors and a gamut of antisocial, aggressive-disruptive behaviors and psychiatric problems.Student classroom misbehavior is linked to student disengagement which correlates with alienation by peers and truancy. Students who misbehaved were reported to perform worse academically which escalated to other severe problems such as dropping out of school and delinquency. Researchers and academicians have designed and implemented intervention programs to reduce this problem. Good intervention program should meet the set criteria. This study aims to discover whether the techniques used by Prophet Muhammad in correcting mistakes of his companions could be applied in managing misbehaviors of primary school students during teaching and learning process; and to determine whether these techniques met the criteria of a good intervention program. Six relevant hadith on correcting mistakes were selected and analyzed to formulate techniques of managing misbehaviors which were implemented in two primary school classrooms by a trained teacher. This qualitative research examined and analysed journals written by the teacher; and the verbatim transcriptions of two one-hour interview sessions with the teacher to assess teacher’s correct application of the techniques and to discover the impact of the techniques on students’ behaviors. Findings revealed that the techniques used were effective in reducing classroom disruptive behaviors; easy to implement; not disrupting the normal classroom activities; and parsimonious. This study contributes to production of knowledge from Islamic worldview; and contributes to the relevantization project which is the mission of International Islamic University Malaysia.